Perancangan Media Video Company Profile Bank Sampah NTB Mandiri - Kadek Risma Yunita (Jurnal SASAK : Desain Visual dan Komunikasi, 2021)
Garbage is one of the problems in Indonesia including in West Nusa Tenggara which has become a global problem, garbage that has accumulated and is not properly processed or handled can cause environmental pollution. One way that can be done to overcome the problem of waste is separating waste according to its type (organic and inorganic), by doing 3R (Reduce, Reuse, Recycle) and also by recycling waste. Currently the handling of waste recycling by the community has been carried out at the Waste Bank. The NTB Mandiri Garbage Bank is a container or place used to save waste, organic waste can be processed into compost while inorganic waste can be recycled into several handicraft items such as bags, tablecloths tables, wallets, key chains, and several other items made of plastic and used tires or other inorganic waste. This waste will later be saved in the form of money and rewarded according to its type. Therefore, a company profile video of the NTB MANDIRI Waste Bank will be designed to help introduce it to the community. Keywords - Video, Company Profile, Waste Bank